Positive electrode active material, positive electrode sheet, secondary battery, and electric device

CN119256400AActive Publication Date: 2025-01-03CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380043315.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-01-03
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

Existing secondary batteries cannot meet the needs of new batteries in terms of energy density and rate performance, especially in the rapid development of electric vehicles and other fields, finding materials with high energy density and excellent rate performance has become an urgent need.

Method used

By controlling the particle size distribution and primary particle size of the agglomerate material, the compaction density of the positive electrode sheet is improved, the migration distance of lithium ions is shortened, the active sites of a large number of lithium ions are exposed, and the appropriate particle size distribution and ratio of the agglomerate material is adopted. The surface area, combined with the particle size distribution of the first and second agglomerates, forms a cathode active material with high capacity and excellent magnification properties.

Benefits of technology

The battery with high energy density and excellent rate performance has been achieved, which meets the needs of new batteries and improves the structural stability and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256400A_ABST
    Figure CN119256400A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode active material, the positive electrode active material comprises an aggregate material, the chemical formula of the aggregate material is LiaNixCoyM1-x-yO2-b, 0.6 < = a < = 1.2, 0.6 < = x < = 1, 0 < = y < = 0.4,-0.1 < = b < = 0.1, and M comprises one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, Nb and Mo; the particle size of primary particles of the aggregate material is 100-600nm, the particle size distribution of the aggregate material meets the condition that (Dv90-Dv10) / Dv50 is greater than or equal to 1.6, and the positive electrode active material can improve the compaction density of a pole piece, improve the energy density of a battery and meet the requirements of a high-energy-density battery.
Need to check novelty before this filing date? Find Prior Art

Description

Positive electrode active material, positive electrode sheet, secondary battery and electrical device Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode active material, a positive electrode plate, a secondary battery, and an electrical device. Background Art

[0002] Since their commercialization, secondary batteries have rapidly become a widely used energy storage device in various fields of life and have attracted widespread interest from experts and researchers due to their advantages such as high energy density, high battery voltage, long cycle life, and lack of memory effect. With the rapid development of electronic and electrical equipment, especially electric vehicles, the energy density and rate performance of existing secondary batteries cannot meet the demand for use. Therefore, the search and preparation of materials with high energy density is an urgent issue.

[0003] Summary of the Invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material. The present application improves the compaction density of the electrode sheet and the energy density of the battery by controlling the particle size distribution and primary particle size of the material. At the same time, the battery has excellent rate performance to meet the use requirements of new batteries.

[0005] The first aspect of the present application provides a positive electrode active material, the positive electrode active material includes an aggregate material, the chemical formula of the aggregate material is Li a Ni x Co y M 1-x-y O 2-b , wherein 0.6≤a≤1.2, 0.6≤x≤1, 0≤y≤0.4, -0.1≤b≤0.1, and M includes one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, Nb, and Mo; the primary particle size of the agglomerate material is 100-600 nm, and the particle size distribution of the agglomerate material satisfies (Dv90-Dv10) / Dv50≥1.6.

[0006] The agglomerate material is controlled to have a larger particle size distribution, and the large and small particles in the agglomerate material cooperate with each other to fill the gaps, making the particles in the positive electrode active material more densely packed, thereby increasing the compaction density of the electrode and the energy density of the lithium-ion battery. At the same time, by controlling the size of the primary particles of the agglomerate material within a suitable range, the migration distance of the lithium ions is shortened, and a large number of active sites of lithium ions are exposed, thereby increasing the gram capacity of the agglomerate material, the battery has excellent rate performance, and the energy density of the material is improved.

[0007] In any embodiment, the chemical formula Li a Nix Co y M 1-x-y In O2, 0.6≤a≤1.2, 0.8≤x≤1, 0≤y≤0.2, -0.1≤b≤0.1, optionally, 0.8≤a≤1.2, 0.93≤x≤0.98, 0≤y≤0.07, -0.1≤b≤0.1.

[0008] The positive electrode active material has high gram capacity and good structural stability, which can make the battery have high energy density and excellent rate performance.

[0009] In any embodiment, the primary particle size of the agglomerate material is 200-500 nm.

[0010] When the primary particle size of the agglomerate material is within a suitable range, more lithium ion reaction active sites are exposed, the gram capacity of the agglomerate material is increased, and the energy density of the battery is increased. The primary particle size within a suitable range can also reduce the side reactions between the electrolyte and the material, and reduce the loss of irreversible capacity.

[0011] In any embodiment, the particle size Dv50 of the agglomerate material is 6-15 μm, optionally 7-13 μm.

[0012] The particle size Dv50 of the agglomerate material is within a suitable range, which is conducive to making the positive electrode sheet have a high compaction density and improving the energy density of the battery. At the same time, the agglomerate material has an appropriate Dv50, which can improve the ionic conductivity and electronic conductivity of the material, and the battery has excellent rate performance.

[0013] In any embodiment, the particle size distribution of the agglomerate material is determined to be unimodal by particle size analysis using a laser diffraction method, with the peak located at 6-15 μm, or optionally 7-13 μm.

[0014] The particle size distribution diagram of the agglomerate material is unimodal, and the position of the unimodal peak is within an appropriate range, which is conducive to making the positive electrode sheet have a high compaction density and improving the energy density of the battery. At the same time, the unimodal peak position within an appropriate range indicates that the material has a suitable particle size, which can improve the ionic conductivity and electronic conductivity of the material and improve the rate performance of the battery.

[0015] In any embodiment, the particle size distribution of the agglomerate material satisfies 1.6≤(Dv90-Dv10) / Dv50≤2.3. Optionally, the particle size distribution of the agglomerate material satisfies 1.8≤(Dv90-Dv10) / Dv50≤2.1.

[0016] The particle size distribution of the agglomerate material is in an appropriate range. On the one hand, it can improve the compaction density of the electrode and the energy density of the battery by grading the particle size. On the other hand, the appropriate particle size distribution can reduce the impact of the presence of too many large or too small particles in the material on the compaction density.

[0017] In any embodiment, the specific surface area of ​​the agglomerate material is 0.5 m 2 / g-0.9m 2 / g.

[0018] When the specific surface area of ​​the aggregate material is within an appropriate range, the migration distance of lithium ions is shortened and the rate performance of the battery is improved. In addition, the appropriate specific surface area can also expose more lithium ion reaction active sites, increase the gram capacity of the electrode, and increase the energy density of the battery. At the same time, the specific surface area within an appropriate range can also reduce the side reactions between the electrolyte and the material and reduce the loss of irreversible capacity.

[0019] In any embodiment, the agglomerate material includes first agglomerates and second agglomerates, the particle size Dv50 of the first agglomerates is 9-15 μm, and the particle size Dv50 of the second agglomerates is 4-8 μm.

[0020] The particle size Dv50 of the first agglomerate and the second agglomerate is within a suitable range, so that the agglomerate material has a suitable particle size distribution, the large and small gaps between the particles can be effectively filled, the agglomerate material is tightly packed, the compaction density of the electrode is increased, and the energy density of the battery is increased.

[0021] In any embodiment, the chemical formula of the first agglomerate is Li a1 Ni x1 Co y1 M1 1-x1- y1 O 2-b1 The chemical formula of the second aggregate is Li a2 Ni x2 Co y2 M2 1-x2-y2 O 2-b2 , x1≥x2,

[0022] Among them, 0.6≤a1≤1.2, 0.6≤x1≤1, 0≤y1≤0.4, -0.1≤b1≤0.1, 0.6≤a2≤1.2, 0.4≤x2≤1, 0≤y2≤0.6, -0.1≤b2≤0.1, and M1 and M2 independently include one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, Nb, and Mo.

[0023] The first aggregate has a large Dv50 and relatively few lithium ion reactive sites. By increasing the nickel content, a high gram capacity can be achieved, thereby increasing the battery's energy density. The second aggregate has a small particle size Dv50 and relatively more lithium ion reactive sites. This allows for a high gram capacity even with a relatively low nickel content. The coordinated interaction of the particle size Dv50 and nickel content of the first and second aggregates improves the battery's energy density.

[0024] In any embodiment, the chemical formula of the first aggregate is Li a1 Ni x1 Co y1 M1 1-x1- y1 O 2-b1 In the equation (a), 0.8≤a1≤1.2, 0.94≤x1≤0.98, 0≤y1≤0.06, and -0.1≤b1≤0.1.

[0025] In any embodiment, the chemical formula of the second aggregate is Li a2 Ni x2 Co y2 M2 1-x2- y2 O 2-b2 In the equation, 0.8≤a2≤1.2, 0.93≤x2≤0.96, 0≤y2≤0.07, -0.1≤b2≤0.1.

[0026] In any embodiment, the primary particle size of the first agglomerate is larger than the primary particle size of the second agglomerate.

[0027] On the premise that the particle size Dv50 of the first agglomerate is greater than the particle size Dv50 of the second agglomerate, controlling the primary particle size of the first agglomerate to be larger than the primary particle size of the second agglomerate can increase the compaction density of the first agglomerate. At the same time, the primary particle size of the second agglomerate is relatively small, shortening the transmission distance of lithium ions, improving the ion conductivity and electronic conductivity of the second agglomerate, and exposing more active sites for lithium ion reactions, thereby comprehensively improving the energy density and rate performance of the battery.

[0028] In any embodiment, the primary particle size of the first agglomerate is 100-1000 nm, and the primary particle size of the second agglomerate is 100-300 nm.

[0029] A suitable primary particle size range of the first agglomerate can increase the compaction density of the electrode and the energy density of the battery. At the same time, a suitable primary particle size range of the second agglomerate is conducive to the utilization of the gram capacity of the second agglomerate and to improving the rate performance of the battery.

[0030] In any embodiment, the particle size distribution of the first agglomerates and the second agglomerates satisfies (Dv90-Dv10) / Dv50≤1.50.

[0031] The particle size distribution of the first agglomerates and the second agglomerates is within an appropriate range, which reduces the influence of the presence of a large number of particles with larger particle sizes or smaller particle sizes in the material on the compaction density.

[0032] In any embodiment, the particle size distribution of the first agglomerates satisfies 0.50≤(Dv90-Dv10) / Dv50≤1.30, and the particle size distribution of the second agglomerates satisfies 1.30≤(Dv90-Dv10) / Dv50≤1.50.

[0033] The particle size distribution of the first agglomerates is within a suitable range and can provide sufficient filling space. The particle size distribution of the second agglomerates is within a suitable range and can fully fill the space between the first agglomerates. The two work together to improve the compaction density.

[0034] In any embodiment, the mass ratio of the first agglomerates to the second agglomerates is 1:1-9:1.

[0035] The first agglomerates have a relatively large particle size (Dv50), acting as a framework. The second agglomerates have a relatively small particle size (Dv50), filling the gaps in the framework. The mass ratio of the first to second agglomerates is within an appropriate range, resulting in an appropriate particle size distribution for the positive electrode active material, which can improve the compaction density of the electrode sheet and increase the energy density of the battery.

[0036] A second aspect of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer comprises the positive electrode active material of the first aspect.

[0037] The positive electrode plate has high compaction density, surface density and low elongation, which improves the gram capacity of the plate and improves the use performance and processing performance of the plate.

[0038] In any embodiment, the mass content of the positive electrode active material is 95% to 99.5%, based on the total mass of the positive electrode film layer.

[0039] The mass content of the positive electrode active material within the above range can increase the gram capacity of the electrode and improve the energy density of the battery.

[0040] In any embodiment, when the compaction density of the positive electrode sheet is 3.5 g / cm 3 -3.8g / cm 3 When the positive electrode sheet has a longitudinal elongation of 7% to 8%.

[0041] The longitudinal elongation of the pole piece within the above range improves the flexibility of the pole piece, reduces the possibility of brittle fracture during the winding or hot pressing process of the pole piece, and improves the performance of the pole piece.

[0042] In any embodiment, the coating area density of the positive electrode film layer is 21.5 mg / cm 2 -32.5mg / cm 2 .

[0043] The coating area density of the positive electrode film layer within the above range can increase the gram capacity of the electrode and improve the energy density of the battery.

[0044] In any embodiment, the compacted density of the positive electrode sheet is 3.5 g / cm 3 -3.8g / cm 3 .

[0045] The compaction density of the positive electrode sheet within the above range can increase the gram capacity of the sheet and improve the energy density of the battery.

[0046] The third aspect of the present application provides a secondary battery, comprising the positive electrode sheet of the second aspect of the present application.

[0047] In any embodiment, the secondary battery comprises a lithium-ion battery.

[0048] A fourth aspect of the present application provides an electrical device comprising the secondary battery of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0050] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;

[0051] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;

[0052] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0053] FIG5 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG4 ;

[0054] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0055] Description of reference numerals:

[0056] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION

[0057] Below, the embodiments of the binder, preparation method, electrode, battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0058] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0059] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0060] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0061] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0062] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0063] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0064] The compaction density, platform voltage and gram capacity of ternary materials have received widespread attention. The positive electrode sheets of ternary materials generally use a compaction density of ≤3.3g / cm 3 , when using compaction density>3.3g / cm 3 When the high nickel ternary cathode is compacted too much, it is easy to cause the secondary particle structure to break or crack. The exposed fresh interface will react with the electrolyte, accelerating the degradation of the battery cell and reducing the battery life and safety performance. When the ternary cathode is compacted too little, it will not contribute much to the improvement of battery energy density, and the energy density will decrease, and the battery range will decrease. Therefore, it is necessary to develop a cathode active material with high compaction density and high energy density to meet the needs of new batteries.

[0065] [Positive electrode active material]

[0066] Based on this, the present application provides a positive electrode active material, which includes an aggregate material, and the chemical formula of the aggregate material is Li a Ni x Co y M 1-x-y O 2-b, wherein 0.6≤a≤1, 0.6≤x≤1, 0≤y≤0.4, -0.1≤b≤0.1, and M includes one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, Nb, and Mo; the primary particle size of the agglomerate material is 100-600 nm, and the particle size distribution of the agglomerate material satisfies (Dv90-Dv10) / Dv50≥1.6.

[0067] In this article, the term "agglomerate" refers to an aggregate formed by the combination of primary particles under the action of interaction forces, and the particles in the agglomerate are called primary particles.

[0068] Herein, the term "primary particles" refers to particles before agglomeration.

[0069] The primary particle size can be measured using methods known in the art. For example, after cold pressing, the sample is cut open using an Ar particle beam to expose the end face. A scanning electron microscope (SEM) image of the end face is then taken. The size of the sample's primary particles is measured based on the SEM image. At least three samples are measured, with at least 50 data points measured for each sample. The number average is taken as the primary particle size of the sample's primary particles.

[0070] As used herein, the term "Dv90" refers to the particle size at which 90% of the volume is accumulated from the smallest particle size side in the volume-based particle size distribution of powder particles.

[0071] As used herein, the term "Dv10" refers to a particle size that represents 10% of the cumulative volume from the smallest particle size side in a volume-based particle size distribution of powder particles.

[0072] In this article, the term "Dv50" refers to the particle size distribution of powder particles based on volume, which is the particle size at which the cumulative volume reaches 50% from the smallest particle size side.

[0073] The particle size distribution Dv10, Dv50, and Dv90 can be measured using methods known in the art. For example, the particle size distribution laser diffraction method according to GB / T 19077-2016 / ISO 13320:2009 can be used, and the measurement can be performed using a Malvern 3000 instrument.

[0074] In some embodiments, M comprises Mn or Al.

[0075] Mn or Al can play a supporting role, providing stability during the charge and discharge process, which is beneficial to improving safety performance.

[0076] In some embodiments, M comprises Sb or Nb.

[0077] Sb or Nb can refine the grains, making the primary particle size of the material smaller, and further improving the material's specific capacity and rate performance.

[0078] In some embodiments, M includes Sr.

[0079] Sr is a flux. On the premise of preparing a suitable particle size, the flux can lower the sintering temperature and reduce the formation of rock salt phase, thereby improving the capacity and cycle life of the material and improving the cycle life of the battery.

[0080] The chemical formula of the aggregate material can be confirmed by testing using methods known in the art. As an example, an inductively coupled plasma spectrometer (ICP) (such as Spectroblue) is used to measure the proportion of each element in the aggregate material to determine the chemical formula of the aggregate material.

[0081] In some embodiments, the primary particle size of the agglomerate material may be any value among 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, or a range consisting of any two values ​​thereof.

[0082] In some embodiments, the particle size distribution of the agglomerate material satisfies any one of (Dv90-Dv10) / Dv50≥1.6, (Dv90-Dv10) / Dv50≥1.7, (Dv90-Dv10) / Dv50≥1.8, (Dv90-Dv10) / Dv50≥1.9, (Dv90-Dv10) / Dv50≥2, (Dv90-Dv10) / Dv50≥2.1, (Dv90-Dv10) / Dv50≥2.2, (Dv90-Dv10) / Dv50≥2.3, and (Dv90-Dv10) / Dv50≥2.4.

[0083] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b , a is any value among 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, or a range consisting of any two values ​​thereof.

[0084] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b , x is any value among 0.6, 0.7, 0.8, 0.85, 0.9, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, or a range consisting of any two values ​​thereof.

[0085] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b , y is any value of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.1, 0.15, 0.2, 0.3, 0.4, or a range consisting of any two values ​​thereof.

[0086] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b In the equation, b is any value among -0.1, 0, 0.1, or a range consisting of any two values ​​therein.

[0087] By controlling the agglomerate material to have a larger particle size distribution, the large and small particles in the agglomerate material cooperate with each other to fill the gaps, which can increase the space between the particles and the volume utilization rate, making the particles in the positive electrode active material more densely packed, improving the compressive resistance of the pole piece, improving the compaction density of the pole piece, and improving the energy density of the lithium-ion battery. At the same time, by controlling the size of the primary particles of the agglomerate material within an appropriate range, the migration distance of the lithium ions is shortened, and a large number of lithium ion active sites are exposed, thereby increasing the gram capacity of the material, the battery has excellent rate performance, and the energy density of the material is increased. In addition, the close stacking of the agglomerate material can also avoid the displacement of particles under high pressure in the pole piece, making the pole piece have a low elongation and improving the flexibility of the pole piece.

[0088] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b In the equation (a), 0.6≤a≤1.2, 0.8≤x≤1, 0≤y≤0.2, and -0.1≤b≤0.1.

[0089] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b , a is any value among 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, or a range consisting of any two values ​​thereof.

[0090] In some embodiments, the chemical formula Li a Ni x Co y M1-x-y O 2-b , x is any value among 0.8, 0.85, 0.9, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, or a range consisting of any two values ​​thereof.

[0091] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b , y is any value among 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.1, 0.15, 0.2, or a range consisting of any two values ​​thereof.

[0092] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b In the equation, b is any value among -0.1, 0, 0.1, or a range consisting of any two values ​​therein.

[0093] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b In the equation (a), 0.8≤a≤1.2, 0.93≤x≤0.98, 0≤y≤0.07, and -0.1≤b≤0.1.

[0094] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b , a is any value among 0.8, 0.9, 1.0, 1.1, 1.2, or a range consisting of any two values ​​therein.

[0095] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b , x is any value among 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, or a range consisting of any two values ​​thereof.

[0096] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b, y is any value among 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, or a range consisting of any two values ​​thereof.

[0097] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y O 2-b In the equation, b is any value among -0.1, 0, 0.1, or a range consisting of any two values ​​therein.

[0098] With the chemical formula within the above range, the aggregate has a high gram capacity and the battery has a high energy density.

[0099] In some embodiments, the primary particle size of the agglomerate material is 200-500 nm.

[0100] In some embodiments, the primary particle size of the agglomerate material is any value among 200 nm, 300 nm, 400 nm, 500 nm, or a range consisting of any two values ​​therein.

[0101] The primary particle size of the agglomerate material is within an appropriate range, exposing more lithium ion reaction active sites, increasing the gram capacity of the agglomerate material, increasing the energy density of the battery, and reducing the side reactions between the electrolyte and the material, reducing the loss of irreversible capacity.

[0102] In some embodiments, the particle size Dv50 of the agglomerate material is 6-15 μm. In some embodiments, the particle size Dv50 of the agglomerate material is any value of 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or a range consisting of any two of these values.

[0103] The particle size Dv50 of the agglomerate material is within an appropriate range, which is conducive to making the positive electrode sheet have a high compaction density and improving the energy density of the battery. At the same time, the agglomerate material has an appropriate Dv50, which can improve the ionic conductivity and electronic conductivity of the material and improve the rate performance of the battery.

[0104] In some embodiments, the particle size Dv50 of the agglomerate material is 7-13 μm. In some embodiments, the particle size Dv50 of the agglomerate material is any value among 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, or a range consisting of any two of these values.

[0105] The particle size Dv50 of the agglomerate material is within a suitable range, which is conducive to making the positive electrode sheet have a high compaction density and improving the energy density of the battery.

[0106] In some embodiments, the particle size distribution of the agglomerate material is determined to be unimodal by particle size analysis using a laser diffraction method, with the peak located at 6-15 μm.

[0107] In this paper, referring to GB / T 19077-2016 / ISO 13320:2009 particle size distribution laser diffraction method, the Malvern 3000 equipment was used for measurement to obtain a particle size distribution diagram based on volume distribution, and the single peak position was measured from the particle size distribution diagram.

[0108] In some embodiments, the single peak position is located at any value of 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or a range consisting of any two of these values.

[0109] The particle size distribution diagram of the agglomerate material is unimodal, and the position of the unimodal peak is within an appropriate range, which is conducive to making the positive electrode sheet have a high compaction density and improving the energy density of the battery. At the same time, the unimodal peak position within an appropriate range indicates that the material has a suitable particle size, which can improve the ionic conductivity and electronic conductivity of the material and improve the rate performance of the battery.

[0110] In some embodiments, the single peak is located at 7-13 μm. In some embodiments, the single peak is located at any value of 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, or a range consisting of any two of these values.

[0111] The single peak position is within an appropriate range, which is beneficial for the positive electrode sheet to have a high compaction density and improve the energy density of the battery.

[0112] In some embodiments, the particle size distribution of the agglomerate material satisfies 1.6≤(Dv90-Dv10) / Dv50≤2.3. In some embodiments, the particle size distribution of the agglomerate material satisfies 1.6≤(Dv90-Dv10) / Dv50≤1.7, 1.6≤(Dv90-Dv10) / Dv50≤1.8, 1.6≤(Dv90-Dv10) / Dv50≤1.9, 1.6≤(Dv90-Dv10) / Dv50≤2.0, 1.6≤(Dv90-Dv10) / Dv50≤2.1, 1.6≤(Dv90-Dv10) / Dv50≤2.2, 1.6≤(Dv90-Dv10) / Dv50≤2.3. Dv10) / Dv50≤2.3, 1.7≤(Dv90-Dv10) / Dv50≤1.8, 1.7≤(Dv90-Dv10) / Dv50≤1.9, 1.7≤(Dv90-Dv10) / Dv50≤2.0, 1 .7≤(Dv90-Dv10) / Dv50≤2.1, 1.7≤(Dv90-Dv10) / Dv50≤2.2, 1.7≤(Dv90-Dv10) / Dv50≤2.3, 1.8≤(Dv90-Dv10) / D v50≤1.9, 1.8≤(Dv90-Dv10) / Dv50≤2.0, 1.8≤(Dv90-Dv10) / Dv50≤2.1, 1.8≤(Dv90-Dv10) / Dv50≤2.2, 1.8≤(Dv9 0-Dv10) / Dv50≤2.3, 1.9≤(Dv90-Dv10) / Dv50≤2.0, 1.9≤(Dv90-Dv10) / Dv50≤2.1, 1.9≤(Dv90-Dv10) / Dv50≤2.2 , any one of 1.9≤(Dv90-Dv10) / Dv50≤2.3, 2.0≤(Dv90-Dv10) / Dv50≤2.1, 2.0≤(Dv90-Dv10) / Dv50≤2.2, 2.0≤(Dv90-Dv10) / Dv50≤2.3, 2.1≤(Dv90-Dv10) / Dv50≤2.2, 2.1≤(Dv90-Dv10) / Dv50≤2.3, and 2.2≤(Dv90-Dv10) / Dv50≤2.3.

[0113] If the particle size distribution of the agglomerate material is within an appropriate range, on the one hand, the compaction density of the electrode can be improved by grading the particle size, and the energy density of the battery can be improved. On the other hand, the appropriate particle size distribution can reduce the impact of the presence of too many large particles or too small particles in the material on the compaction density, and can also avoid the pulverization of too small particles during the cycle process, causing the deterioration of the battery cell. In addition, too many large particles or too small particles will also affect the preparation of the positive electrode slurry, and the slurry is prone to gelation, which affects the processing performance of the slurry.

[0114] In some embodiments, the particle size distribution of the agglomerate material satisfies 1.8≤(Dv90-Dv10) / Dv50≤2.1. In some embodiments, the particle size distribution of the agglomerate material satisfies any one of 1.8≤(Dv90-Dv10) / Dv50≤1.9, 1.8≤(Dv90-Dv10) / Dv50≤2.0, 1.8≤(Dv90-Dv10) / Dv50≤2.1, 1.9≤(Dv90-Dv10) / Dv50≤2.0, 1.9≤(Dv90-Dv10) / Dv50≤2.1, and 2.0≤(Dv90-Dv10) / Dv50≤2.1.

[0115] The particle size distribution of the agglomerates is within a suitable range, and the positive electrode sheet has a suitable compaction density, thereby improving the energy density of the battery.

[0116] In some embodiments, the specific surface area of ​​the agglomerate material is 0.5 m 2 / g-0.9m 2 In some embodiments, the specific surface area of ​​the aggregate material can be 0.5 m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 Any value in / g or a range consisting of any two values ​​in it.

[0117] The specific surface area can be measured using any method known in the art. For example, reference can be made to GB / T 19587-2017, "Determination of Specific Surface Area of ​​Solids by BET Method for Gas Adsorption," using a TriStar II 3020 instrument.

[0118] When the specific surface area of ​​the aggregate material is within an appropriate range, the migration distance of lithium ions is shortened and the rate performance of the battery is improved. In addition, the appropriate specific surface area can also expose more lithium ion reaction active sites, increase the gram capacity of the electrode, and increase the energy density of the battery. At the same time, the specific surface area within an appropriate range can also reduce the side reactions between the electrolyte and the material and reduce the loss of irreversible capacity.

[0119] In some embodiments, the agglomerate material includes first agglomerates and second agglomerates, the particle size Dv50 of the first agglomerates is 9-15 μm, and the particle size Dv50 of the second agglomerates is 4-8 μm.

[0120] In some embodiments, the particle size Dv50 of the first agglomerates is any value of 9 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or a range consisting of any two values ​​thereof.

[0121] In some embodiments, the particle size Dv50 of the second agglomerates is any value of 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or a range consisting of any two values ​​thereof.

[0122] The particle size Dv50 of the first agglomerate and the second agglomerate refers to the test method for the particle size Dv50 of the agglomerate material.

[0123] The first agglomerate with a relatively large particle size Dv50 can serve as the skeleton of the electrode. The appropriate particle size Dv50 can avoid cracks at the edges of large particles and improve the service life of the battery. The second agglomerate with a relatively small particle size Dv50 can serve as a filler for the skeleton of the first agglomerate to improve space utilization.

[0124] The particle size Dv50 of the first agglomerate and the second agglomerate is within a suitable range, so that the agglomerate material has a suitable particle size distribution, the large and small gaps between the particles can be effectively filled, the agglomerate material is tightly packed, the compaction density of the electrode is increased, and the energy density of the battery is increased.

[0125] In some embodiments, the chemical formula of the first aggregate is Li a1 Ni x1 Co y1 M1 1-x1- y1 O 2-b1 The chemical formula of the second aggregate is Li a2 Ni x2 Co y2 M2 1-x2-y2 O 2-b2 , x1≥x2,

[0126] Among them, 0.6≤a1≤1.2, 0.6≤x1≤1, 0≤y1≤0.4, -0.1≤b1≤0.1, 0.6≤a2≤1.2, 0.4≤x2≤1, 0≤y2≤0.6, -0.1≤b2≤0.1, and M1 and M2 independently include one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, Nb, and Mo.

[0127] In some embodiments, M1 or M2 each independently comprises Mn or Al.

[0128] In some embodiments, the chemical formula Li a1 Ni x1 Co y1 M1 1-x1-y1 O 2-b1 , a1 is any value among 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, or a range consisting of any two values ​​thereof.

[0129] In some embodiments, the chemical formula Li a1 Ni x1 Co y M1 1-x1-y1 O 2-b1 , x1 is any value among 0.6, 0.7, 0.8, 0.85, 0.9, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, or a range consisting of any two of these values.

[0130] In some embodiments, the chemical formula Li a1 Ni x1 Co y1 M1 1-x1-y1 O 2-b1 , y1 is any value among 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.1, 0.15, 0.2, 0.3, 0.4, or a range consisting of any two values ​​therein.

[0131] In some embodiments, the chemical formula Li a1 Ni x1 Co y1 M1 1-x1-y1 O 2-b1 In the equation, b1 is any value among -0.1, 0, 0.1, or a range consisting of any two values ​​therein.

[0132] In some embodiments, the chemical formula Li a2 Ni x2 Co y2 M2 1-x2-y2 O 2-b2 , a2 is any value among 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, or a range consisting of any two values ​​thereof.

[0133] In some embodiments, the chemical formula Li a2 Ni x2 Co y2 M2 1-x2-y2 O 2-b2 , x2 is any value among 0.4, 0.5, 0.6, 0.7, 0.8, 0.85, 0.9, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, or a range consisting of any two of these values.

[0134] In some embodiments, the chemical formula Li a2 Ni x2 Co y2 M2 1-x2-y2 O 2-b2, y2 is any value of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.1, 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, or a range consisting of any two of these values.

[0135] In some embodiments, the chemical formula Li a2 Ni x2 Co y2 M1 1-x2-y2 O 2-b2 In the example, b2 is

[0136] Any value among -0.1, 0, 0.1, or a range consisting of any two of these values.

[0137] The confirmation of the chemical formula of the first agglomerate and the second agglomerate refers to the test method for confirmation of the chemical formula of the agglomerate material.

[0138] The first agglomerate has a large particle size Dv50 and relatively few lithium ion reactive sites. By increasing the nickel content, a high gram capacity can be achieved, thereby increasing the battery's energy density. The second agglomerate has a small particle size Dv50 and relatively more lithium ion reactive sites. With a relatively low nickel content, a high gram capacity can be achieved. The coordinated coordination of the particle size Dv50 and nickel content of the first and second agglomerates improves the battery's energy density.

[0139] In some embodiments, the chemical formula of the first aggregate is Li a1 Ni x1 Co y1 M1 1-x1- y1 O 2-b1 In the equation (a), 0.8≤a1≤1.2, 0.94≤x1≤0.98, 0≤y1≤0.06, and -0.1≤b1≤0.1.

[0140] In some embodiments, a1 is any value of 0.8, 0.9, 1.0, 1.1, 1.2, or a range consisting of any two values ​​thereof.

[0141] In some embodiments, x1 is any value of 0.94, 0.95, 0.96, 0.97, 0.98, or a range consisting of any two values ​​thereof.

[0142] In some embodiments, y1 is any value of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, or a range consisting of any two values ​​thereof.

[0143] In some embodiments, b1 is any value among -0.1, 0, 0.1, or a range consisting of any two values ​​therein.

[0144] In some embodiments, the chemical formula of the second aggregate is Li a2 Ni x2 Co y2 M2 1-x2- y2 O 2-b2 In the equation, 0.8≤a2≤1.2, 0.93≤x2≤0.96, 0≤y2≤0.07, -0.1≤b2≤0.1.

[0145] In some embodiments, a2 is any value selected from 0.8, 0.9, 1.0, 1.1, and 1.2, or a range consisting of any two values ​​thereof.

[0146] In some embodiments, x2 is any value selected from 0.93, 0.94, 0.95, 0.96, or a range consisting of any two values ​​thereof.

[0147] In some embodiments, y2 is any value of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, or a range consisting of any two values ​​thereof.

[0148] In some embodiments, b2 is any value among -0.1, 0, 0.1, or a range consisting of any two values ​​therein.

[0149] When the chemical formulas of the first aggregate and the second aggregate are within the above ranges, the first aggregate and the second aggregate have high gram capacity, and the battery has high energy density.

[0150] In some embodiments, the primary particle size of the first agglomerate is larger than the primary particle size of the second agglomerate.

[0151] On the premise that the particle size Dv50 of the first agglomerate is greater than the particle size Dv50 of the second agglomerate, controlling the primary particle size of the first agglomerate to be larger than the primary particle size of the second agglomerate can increase the compaction density of the first agglomerate. At the same time, the primary particle size of the second agglomerate is relatively small, shortening the transmission distance of lithium ions, improving the ion conductivity and electronic conductivity of the second agglomerate, and exposing more active sites for lithium ion reactions, thereby comprehensively improving the energy density and rate performance of the battery.

[0152] In some embodiments, the primary particle size of the first agglomerate is 100-1000 nm, and the primary particle size of the second agglomerate is 100-300 nm.

[0153] In some embodiments, the primary particle size of the first agglomerate is any value of 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or a range consisting of any two values ​​thereof.

[0154] In some embodiments, the primary particle size of the second agglomerates is any value of 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, or a range consisting of any two of these values.

[0155] The test method of primary particle size of the first agglomerate and the second agglomerate refers to the test method of primary particle size of agglomerate material.

[0156] A suitable primary particle size range of the first agglomerate can increase the compaction density of the electrode and the energy density of the battery. At the same time, a suitable primary particle size range of the second agglomerate is conducive to the utilization of the gram capacity of the second agglomerate and to improving the rate performance of the battery.

[0157] In some embodiments, the particle size distribution of the first agglomerates and the second agglomerates satisfies (Dv90-Dv10) / Dv50≤1.50.

[0158] In some embodiments, the particle size distribution of the first agglomerate satisfies (Dv90-Dv10) / Dv50≤0.4, (Dv90-Dv10) / Dv50≤0.5, (Dv90-Dv10) / Dv50≤0.6, (Dv90-Dv10) / Dv50≤0.7, (Dv90-Dv10) / Dv50≤0.8, (Dv90-Dv10) / Dv50≤0.9, (Dv90-Dv10) / Dv50≤0.10, (Dv90-Dv10) / Dv50≤0.11, (Dv90-Dv10) / Dv50≤0.12, (Dv90-Dv10) / Dv50≤0.13, (Dv90-Dv10) / Dv50≤0.14, (Dv90-Dv10) / Dv50≤0.15, (Dv90-Dv10) / Dv50≤0.16, (Dv90-Dv10) / Dv50≤0.17, (Dv90-Dv10) / Dv50≤0.18, (Dv90-Dv10) / Dv50≤0.19, (Dv90-Dv10) / Dv50≤0.20, (Dv90-Dv10) / Dv50≤0.21 Any one of 0≤0.9, (Dv90-Dv10) / Dv50≤1.0, (Dv90-Dv10) / Dv50≤1.1, (Dv90-Dv10) / Dv50≤1.2, (Dv90-Dv10) / Dv50≤1.3, (Dv90-Dv10) / Dv50≤0.4, 0.6≤(Dv90-Dv10) / Dv50≤1.5.

[0159] In some embodiments, the particle size distribution of the second agglomerate satisfies (Dv90-Dv10) / Dv50≤0.4, (Dv90-Dv10) / Dv50≤0.5, (Dv90-Dv10) / Dv50≤0.6, (Dv90-Dv10) / Dv50≤0.7, (Dv90-Dv10) / Dv50≤0.8, (Dv90-Dv10) / Dv50≤0.9, (Dv90-Dv10) / Dv50≤0.10, (Dv90-Dv10) / Dv50≤0.11, (Dv90-Dv10) / Dv50≤0.12, (Dv90-Dv10) / Dv50≤0.13, (Dv90-Dv10) / Dv50≤0.14, (Dv90-Dv10) / Dv50≤0.15, (Dv90-Dv10) / Dv50≤0.16, (Dv90-Dv10) / Dv50≤0.17, (Dv90-Dv10) / Dv50≤0.18, (Dv90-Dv10) / Dv50≤0.19, (Dv90-Dv10) / Dv50≤0.20, (Dv90-Dv10) / Dv50≤0.21 Any one of 0≤0.9, (Dv90-Dv10) / Dv50≤1.0, (Dv90-Dv10) / Dv50≤1.1, (Dv90-Dv10) / Dv50≤1.2, (Dv90-Dv10) / Dv50≤1.3, (Dv90-Dv10) / Dv50≤0.4, 0.6≤(Dv90-Dv10) / Dv50≤1.5.

[0160] The particle size distribution of the first agglomerate and the second agglomerate refers to the test method for agglomerate materials.

[0161] The particle size distribution of the first agglomerates and the second agglomerates is within a suitable range, which reduces the influence of the presence of larger particles or smaller particles in the material on the compaction density. The battery has a high compaction density and a high energy density.

[0162] In some embodiments, the particle size distribution of the first agglomerates satisfies 0.50≤(Dv90-Dv10) / Dv50≤1.30, and the particle size distribution of the second agglomerates satisfies 1.30≤(Dv90-Dv10) / Dv50≤1.50.

[0163] In some embodiments, the particle size distribution of the first agglomerate satisfies 0.50≤(Dv90-Dv10) / Dv50≤0.6, 0.50≤(Dv90-Dv10) / Dv50≤0.7, 0.50≤(Dv90-Dv10) / Dv50≤0.8, 0.50≤(Dv90-Dv10) / Dv50≤0.9, 0.50≤(Dv90-Dv10) / Dv50≤1.0, 0.50≤(Dv90-Dv10) / Dv50≤1.1, 0.50≤(Dv90-Dv10) / Dv50≤1.2, 0.50≤(Dv90-Dv10) / Dv50≤1.3, 0.6≤(Dv90-Dv10) / Dv50≤0.7、0.6≤(Dv90-Dv10) / Dv50≤0.8、0.6≤(Dv90-Dv10) / Dv50≤0.9、0.6≤(Dv90-Dv10) / Dv50≤1.0、0.6≤(Dv90-Dv10) / Dv50≤1.1、0.6≤(Dv90-Dv10) / Dv50≤1.2、0.6≤(Dv90-Dv10) / Dv50≤1.3、0.7≤(Dv90-Dv10) / Dv50≤0.8、0.7≤(Dv90-Dv10) / Dv50≤0.9、0.7≤(Dv90-Dv10) / Dv50≤1.0、0.7≤(Dv90- Dv10) / Dv50≤1.1, 0.7≤(Dv90-Dv10) / Dv50≤1.2, 0.7≤(Dv90-Dv10) / Dv50≤1.3, 0.8≤(Dv90-Dv10) / Dv50≤0.9, 0.8≤(Dv90-Dv10) / Dv50 ≤1.0, 0.8≤(Dv90-Dv10) / Dv50≤1.1, 0.8≤(Dv90-Dv10) / Dv50≤1.2, 0.8≤(Dv90-Dv10) / Dv50≤1.3, 0.9≤(Dv90-Dv10) / Dv50≤1.0, 0.9≤( Any one of: Dv90-Dv10) / Dv50≤1.1, 0.9≤(Dv90-Dv10) / Dv50≤1.2, 0.9≤(Dv90-Dv10) / Dv50≤1.3, 1≤(Dv90-Dv10) / Dv50≤1.1, 1≤(Dv90-Dv10) / Dv50≤1.2, 1≤(Dv90-Dv10) / Dv50≤1.3, 1.1≤(Dv90-Dv10) / Dv50≤1.2, 1.1≤(Dv90-Dv10) / Dv50≤1.3, 1.2≤(Dv90-Dv10) / Dv50≤1.3.

[0164] In some embodiments, the particle size distribution of the second agglomerates satisfies 1.30≤(Dv90-Dv10) / Dv50≤1.50.

[0165] In some embodiments, the particle size distribution of the second agglomerates satisfies any one of 1.30≤(Dv90-Dv10) / Dv50≤1.40, 1.30≤(Dv90-Dv10) / Dv50≤1.5, and 1.40≤(Dv90-Dv10) / Dv50≤1.50.

[0166] The particle size distribution of the first agglomerates is within a suitable range, which can provide sufficient filling space. The particle size distribution of the second agglomerates is within a suitable range, which can fully fill the space between the first agglomerates. The cooperation between the two can improve the compaction density and the energy density of the battery.

[0167] In some embodiments, the mass ratio of the first agglomerates to the second agglomerates is 1:1-9:1.

[0168] In some embodiments, the mass ratio of the first agglomerate to the second agglomerate is any value of 1:1, 2:1, 3:1, 4:1, 5:1, 5:1, 7:1, 8:1, 9:1, or a range consisting of any two values ​​thereof.

[0169] The first aggregates have a relatively large particle size (Dv50), acting as a framework. The second aggregates have a relatively small particle size (Dv50), filling the gaps in the framework. A suitable mass ratio of the first to second aggregates ensures a suitable particle size distribution for the positive electrode active material, increasing the compaction density of the electrode sheet and the energy density of the battery. Furthermore, the smaller second aggregates have relatively low mechanical strength, making them more susceptible to breakage under the action of the roller. A suitable mass ratio of the first to second aggregates improves the structural stability of the material and enhances the safety of the battery.

[0170] In some embodiments, the gram capacity of the positive electrode active material is 230-245 mAh / g.

[0171] The gram capacity of the positive electrode active material can be measured using any method known in the art. For example, a secondary battery is discharged at a constant current of 0.33C to 2.8V and allowed to rest for 30 minutes. It is then charged at a constant current of 0.33C to 4.25V, then charged at a constant current of 0.05C until the voltage stabilizes, and allowed to rest for 30 minutes. The battery is then discharged at a constant current of 0.33C to 2.8V. The discharge capacity is then read and the ratio of the secondary battery's initial discharge capacity to the mass of the positive electrode active material is calculated, recorded as the gram capacity of the positive electrode active material, where 1C = 230 mAh.

[0172] [Positive electrode]

[0173] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer formed on at least a portion of the surface of the positive electrode current collector. The positive electrode film layer includes a positive electrode active material in some embodiments.

[0174] The positive electrode plate has high compaction density, surface density and low elongation, which improves the gram capacity of the plate and improves the use performance and processing performance of the plate.

[0175] In some embodiments, the mass content of the positive electrode active material is 95% to 99.5%, based on the total mass of the positive electrode film layer. In some embodiments, the mass content of the positive electrode active material is any value selected from 95%, 96%, 97%, 98%, 99%, and 99.5%, or a range consisting of any two of these values, based on the total mass of the positive electrode film layer.

[0176] The mass content of the positive electrode active material within the above range can increase the gram capacity of the electrode and improve the energy density of the battery.

[0177] In some embodiments, when the compaction density of the positive electrode sheet is 3.5 g / cm 3 -3.8g / cm 3 When the positive electrode sheet has a longitudinal elongation of 7% to 8%, the longitudinal elongation of the positive electrode sheet is 7%, 7.5%, 8%, or any other value selected from the group consisting of any two of these values.

[0178] The longitudinal elongation of the positive electrode sheet can be tested using any method known in the art. As an example, a 1m length of the positive electrode sheet before cold pressing is cut, marked at both ends, and the pressure is adjusted to the target compaction density. After cold pressing, the distance between the two ends of the positive electrode sheet is recorded as L. The elongation of the sheet is (L-1) / 1*100%.

[0179] The longitudinal elongation of the pole piece within the above range improves the flexibility of the pole piece, reduces the possibility of brittle fracture during the winding or hot pressing process of the pole piece, and improves the performance of the pole piece.

[0180] In some embodiments, the coating area density of the positive electrode film layer is 21.5 mg / cm 2 - 32.5 mg / cm 2 In some embodiments, the coating area density of the positive electrode film layer is 21.5 mg / cm 2 , 24mg / cm 2 , 26mg / cm 2 , 28mg / cm 2 、30mg / cm 2 、32mg / cm 2 、32.5mg / cm 2Any value in , or a range of any two values ​​in .

[0181] The coating area density of the positive electrode film layer is tested by any means known in the art. As an example, the coating area density of the positive electrode film layer is measured by measuring the coating weight (g) of the positive electrode film layer on one side and the coating area (cm 2 Specifically, the coating area density of the positive electrode film layer = the coating weight of the positive electrode film layer on one side (g) / the coating area of ​​the positive electrode film layer (cm 2 ).

[0182] The coating area density of the positive electrode film layer within the above range can increase the gram capacity of the electrode and improve the energy density of the battery.

[0183] In some embodiments, the compacted density of the positive electrode sheet is 3.5 g / cm 3 -3.8g / cm 3 In some embodiments, the compacted density of the positive electrode sheet is 3.5 g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 Any value in , or a range of any two values ​​in .

[0184] The compaction density of the positive electrode sheet can be tested by any means known in the art. As an example, the compaction density PD of the positive electrode sheet is measured by measuring the surface density (g / cm 2 ) and the thickness of the positive electrode film on one side (cm) (the number of collection points is greater than 14). Specifically, the compaction density of the positive electrode sheet PD = the density of the positive electrode film on one side (g / cm 2 ) / thickness of positive electrode film (cm).

[0185] The compaction density of the positive electrode sheet within the above range can increase the gram capacity of the sheet and improve the energy density of the battery.

[0186] The positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The conductive agent may be selected from one or more of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers.

[0187] The positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and optional conductive agent to the positive electrode current collector. The binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA), and carboxymethyl chitosan (CMCS).

[0188] The positive electrode current collector can be a conductive carbon sheet, metal foil, carbon-coated metal foil, porous metal plate, or a composite current collector. The conductive carbon material of the conductive carbon sheet can be selected from one or more of Super P, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers. The metal material of the metal foil, carbon-coated metal foil, and porous metal plate can each be independently selected from at least one of copper, aluminum, nickel, and stainless steel. The composite current collector can be a composite of metal foil and a polymer-based film.

[0189] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0190] [Negative electrode]

[0191] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0192] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0193] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0194] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0195] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0196] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0197] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0198] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0199] [Electrolytes]

[0200] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0201] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0202] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0203] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0204] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0205] [Isolation film]

[0206] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0207] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0208] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0209] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0210] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0211] [Secondary battery]

[0212] In some embodiments, the energy density of the secondary battery is 360-510 Wh / kg.

[0213] In some embodiments, the energy density of the secondary battery is any value of 360Wh / kg, 380Wh / kg, 400Wh / kg, 420Wh / kg, 440Wh / kg, 460Wh / kg, 480Wh / kg, 500Wh / kg, 510Wh / kg, or a range consisting of any two of these values.

[0214] The energy density of the secondary battery is tested by any means known in the art. As an example, the battery cell is left at rest at 25°C for 2 hours to ensure that the temperature of the battery cell is 25°C. At 25°C, after charging the battery cell to the charge cut-off voltage at 0.1C, continue to charge at a constant voltage at the charge cut-off voltage until the current reaches 0.05C and the charging is cut off (where C represents the rated capacity of the battery cell). The battery cell is left at rest at 25°C for 1 hour. At 25°C, the battery cell is discharged to the discharge cut-off voltage at 0.1C, and the total discharge capacity C0 released by the battery cell is recorded. The total discharge energy is E0.

[0215] Battery cell weight measurement: Place the battery cell on an electronic balance until the weight stabilizes, and read the battery cell weight value M0.

[0216] Energy density calculation: Battery cell discharge energy E0 / battery cell weight M0 is the energy density of the battery cell.

[0217] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 is an example of a secondary battery 5 having a square structure, and FIG2 is an exploded view of the secondary battery 5 .

[0218] In some embodiments, referring to Figure 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The non-Newtonian fluid electrolyte composition is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0219] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0220] Figure 3 shows an example battery module 3. Referring to Figure 3 , within the battery module 3, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 3. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured using fasteners.

[0221] Optionally, the battery module 3 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0222] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0223] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0224] [Electrical devices]

[0225] In one embodiment of the present application, an electric device is provided, comprising at least one of a secondary battery according to any embodiment, a battery module according to any embodiment, or a battery pack according to any embodiment.

[0226] The electrical device includes at least one of the secondary batteries, battery modules, or battery packs provided in this application. The secondary batteries, battery modules, or battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0227] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0228] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0229] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0230] Example

[0231] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0232] Example 1

[0233] 1) Preparation of aggregate materials

[0234] The first agglomerate: lithium hydroxide, Ni 0.94 Co 0.05 Mn 0.01 (OH)2 was mixed evenly in a mixer and sintered at 750℃ for 20h in an oxygen atmosphere to obtain the first agglomerate, wherein lithium hydroxide, Ni 0.94 Co 0.05 Mn 0.01 The molar ratio of (OH)2 is 1.04:1.

[0235] The second aggregate: lithium hydroxide, Ni 0.93 Co 0.05 Mn 0.02 (OH)2 was mixed evenly in a mixer and sintered at 800℃ for 20h in an oxygen atmosphere to obtain the second agglomerate, wherein lithium hydroxide, Ni 0.93 Co 0.05 Mn 0.02 The molar ratio of (OH)2 is 1.05:1.

[0236] The first agglomerate and the second agglomerate were mixed in a mass ratio of 7:3 to form an agglomerate material.

[0237] 2) Preparation of positive electrode sheet

[0238] The aggregate material prepared in Example 1 was placed in a 5L mixing tank. The conductive agent, acetylene black (SP), and the binder, polyvinylidene fluoride (PVDF), were premixed for 30 minutes. Then, N-methylpyrrolidone (NMP) was added as a solvent and rapidly stirred under vacuum to form a slurry. The mass ratio of aggregate material: acetylene black: PVDF was 96:2:2, and the solids content of the slurry was 70%. The slurry was evenly coated on both sides of a 12μm-thick positive electrode current collector. The resulting positive electrode sheets were then dried, cold-pressed, and slit.

[0239] 3) Preparation of negative electrode sheet

[0240] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener carbon methyl cellulose sodium (CMC) are fully stirred and mixed in a deionized water solvent system in a weight ratio of 90:5:2:2:1, and then coated on copper foil, dried, and cold pressed to obtain a negative electrode sheet.

[0241] The negative electrode active material, graphite, silicon-carbon material, carbon black (SP), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) are dissolved in deionized water at a weight ratio of 90:4:4:2. A uniformly dispersed negative electrode slurry is obtained by stirring. The negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil. After drying, cold pressing, and cutting, the negative electrode sheet is obtained. Based on the total weight of graphite and silicon-carbon materials, the weight of silicon-carbon materials accounts for 30%.

[0242] 4) Diaphragm

[0243] Polypropylene film is used as the isolation film.

[0244] 5) Preparation of electrolyte

[0245] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7, LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred evenly to make the mass content of LiPF6 lithium salt 12.5%, thereby obtaining the electrolyte of Example 1.

[0246] 6) Preparation of batteries

[0247] The positive electrode sheet, isolation film, and negative electrode sheet of Example 1 are stacked in order, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell. The tabs are welded to the bare battery cell, and the bare battery cell is placed in an aluminum shell and baked at 80°C to remove water. Then, the electrolyte is injected and sealed to obtain an uncharged battery.

[0248] The uncharged battery is then subjected to the following steps: standing, hot and cold pressing, formation, shaping, and capacity testing to obtain the lithium-ion battery product of Example 1.

[0249] The preparation parameters in Examples 2 to 20 and Comparative Examples 1 to 3 are basically the same as those in Example 1. The specific parameters are shown in Tables 1 and 2.

[0250] 2. Test Method

[0251] 1. Characterization of positive electrode active materials

[0252] 1) Confirmation of the chemical formula of the aggregate material, the first aggregate, and the second aggregate

[0253] An inductively coupled plasma spectrometer (ICP) (such as Spectroblue) is used to measure the proportion of each element in the sample and determine the chemical formula of the sample.

[0254] 2) Primary particle size of aggregate material, first aggregate, and second aggregate

[0255] SEM testing: After cold pressing, the sample is cut open using an Ar particle beam to expose the end face. Scanning electron microscopy (SEM) is used to obtain an image of the end face. The size of the sample's primary particles is measured based on the SEM image. At least three samples are measured, with at least 50 data points per sample. The number average is taken as the primary particle size of the sample.

[0256] 3) Agglomerate material, first agglomerate, and second agglomerate D V 50 and (Dv90- Dv10) / Dv50

[0257] Volume distribution particle sizes Dv10, Dv50, and Dv90 are well-known concepts in the art. Specifically, Dv10 is the particle size at which the cumulative volume percentage of a powder particle, starting from the smallest particle size, reaches 10%, typically expressed in μm. Dv50 is the particle size at which the cumulative volume percentage of a powder particle, starting from the smallest particle size, reaches 50%, based on the volume distribution. Dv90 is the particle size at which the cumulative volume percentage of a powder particle, starting from the smallest particle size, reaches 90%, based on the volume distribution.

[0258] The particle size distribution Dv10, Dv50, and Dv90 can be measured using methods known in the art. For example, the particle size distribution laser diffraction method according to GB / T 19077-2016 / ISO 13320:2009 can be used, and the measurement can be performed using a Malvern 3000 instrument.

[0259] 4) Single peak position of particle size distribution

[0260] With reference to GB / T 19077-2016 / ISO 13320:2009 particle size distribution laser diffraction method, the measurement was performed using the Malvern 3000 device to obtain a particle size distribution diagram based on volume distribution, and the single peak position was measured from the particle size distribution diagram.

[0261] 5) Specific surface area of ​​aggregate material

[0262] The BET test method for specific surface area can be performed using methods known in the art. For example, reference can be made to GB / T 19587-2017 "Determination of Specific Surface Area of ​​Solids by Gas Adsorption BET Method," using a TriStar II 3020 instrument.

[0263] 2. Positive electrode

[0264] 1) Coating surface density of the positive electrode film

[0265] The coating density of the positive electrode film layer is obtained by measuring the coating weight (g) of the positive electrode film layer on one side and the coating area (cm 2 Specifically, the coating area density of the positive electrode film layer = the coating weight of the positive electrode film layer on one side (g) / the coating area of ​​the positive electrode film layer (cm 2 ).

[0266] 2) Compaction density of positive electrode

[0267] The compaction density PD of the positive electrode sheet is determined by measuring the surface density (g / cm2) and thickness (cm) of the positive electrode film layer on one side (the number of sampling points is greater than 14). Specifically, the compaction density PD of the positive electrode sheet = the surface density (g / cm2) of the positive electrode film layer on one side 2 ) / thickness of positive electrode film (cm).

[0268] 3) Lengthwise elongation of the positive electrode

[0269] Take the positive electrode sheet before cold pressing, cut a 1m length, mark the two end points, adjust the pressure to the target compaction density, and after cold pressing, take the positive electrode sheet and test the distance between the two end points and record it as L. The elongation of the sheet is (L-1) / 1*100%.

[0270] 3. Battery

[0271] 1) Battery mass energy density

[0272] Battery cell capacity test: Allow the battery cell to rest at 25°C for 2 hours, ensuring the cell temperature is 25°C. At 25°C, charge the battery cell at 0.1C to the charge cutoff voltage. Continue constant voltage charging at the same charge cutoff voltage until the current reaches 0.05C, at which point the charge is cutoff (where C represents the rated capacity of the battery cell). Allow the battery cell to rest at 25°C for 1 hour. At 25°C, discharge the battery cell at 0.1C to the discharge cutoff voltage. Record the total discharge capacity (C0) and the total discharge energy (E0).

[0273] Battery cell weight measurement: Place the battery cell on an electronic balance until the weight stabilizes, and read the battery cell weight value M0.

[0274] Energy density calculation: Battery cell discharge energy E0 / battery cell weight M0 is the energy density of the battery cell.

[0275] 2) Battery discharge time at 40% SOC at 4.5C

[0276] The battery cell was discharged at a constant current of 0.33C to 2.8V and allowed to stand for 30 minutes; charged at a constant current of 0.33C to 4.25V and then at a constant voltage of 0.05C until the voltage stabilized and allowed to stand for 30 minutes; discharged at a constant current of 0.33C to 2.8V, at which time the initial capacity C0 was read and allowed to stand for 30 minutes; charged at a constant current of 0.33C to 4.25V and then at a constant voltage of 0.05C until the voltage stabilized and allowed to stand for 30 minutes; discharged at a constant current of 0.33C to 0.4C0Ah (40%) SOC and allowed to stand for 60 minutes; discharged at a constant current of 4.5C to 2.8V and recorded the discharge time.

[0277] 3. Analysis of test results of various embodiments and comparative examples

[0278] Batteries of various embodiments and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1, 2, and 3 below.

[0279] Table 1

[0280] Table 3

[0281] According to the above results, the positive electrode active materials in Examples 1 to 20 include aggregate materials, and the chemical formula of the aggregate materials is LiNi 0.937 Co 0.05 Mn 0.013 O2、LiNi 0.9375 Co 0.04 Mn 0.0225 O2、LiNi 0.9375 Co 0.0475 Mn 0.015 O2、LiNi 0.948 Co 0.042 Mn 0.01 O2、LiNi 0.95 Co 0.033 Mn 0.017 O2、LiNi 0.959 Co 0.039 Mn 0.002 O2、LiNi 0.96 Co 0.02 Mn0.02 O2,

[0282] LiNi 0.967 Co 0.02 Mn 0.013 O2、LiNi 0.967 Co 0.0255 Mn 0.0075 O2、LiNi 0.95 Co 0.037 Mn 0.013 O2、LiNi 0.953 Co 0.033 Mn 0.014 O2、LiNi 0.96 Co 0.033 Mn 0.007 O2、LiNi 0.951 Co 0.029 Mn 0.02 O2、LiNi 0.936 Co 0.046 Mn 0.018 O2、LiNi 0.94 Co 0.04 Mn 0.02 O2、LiNi 0.94 Co 0.05 Mn 0.01 O2、LiNi 0.942 Co 0.044 Mn 0.014 O2、LiNi 0.945 Co 0.0325 Mn 0.0225 O2、LiNi 0.954 Co 0.04 Mn 0.006 O2 or LiNi 0.955 Co 0.0275 Mn 0.0175 O2, the primary particle size of the agglomerate material is 100-600nm, and the particle size distribution of the agglomerate material satisfies (Dv90-Dv10) / Dv50≥1.6.

[0283] From the comparison of Examples 1 to 20 with Comparative Examples 1 to 3, it can be seen that the primary particle size of the agglomerate material is 100-600 nm, and the particle size distribution of the agglomerate material satisfies (Dv90-Dv10) / Dv50≥1.6, which can increase the compaction density of the electrode and the energy density of the battery, and the battery has excellent rate performance, meeting the use requirements of the new battery.

[0284] From the comparison between Examples 8-10 and Examples 6-7, it can be seen that the primary particle size of the agglomerate material is 200-500 nm, which can further improve the energy density of the battery.

[0285] As can be seen from Examples 1 to 20, the particle size Dv50 of the agglomerate material is 6-15 μm, the pole piece has a high compaction density and low elongation, the battery has a high energy density and excellent rate performance, and the electrochemical performance of the battery is comprehensively improved.

[0286] From the comparison of Examples 12, 14 to 16, and 18 to 20 with Examples 11, 13, and 17, it can be seen that the particle size Dv50 of the agglomerate material is 7-13 μm, which can further improve the energy density of the battery, and the battery has excellent rate performance.

[0287] It can be seen from Examples 1 to 20 that the particle size distribution of the agglomerate material determined by the particle size analysis laser diffraction method is unimodal, with the unimodal peak located at 6-15 μm. The pole piece has a high surface density and low elongation, and the battery has a high energy density and excellent rate performance, which comprehensively improves the electrochemical performance of the battery.

[0288] From the comparison of Examples 12, 14 to 16, 18 to 20 with Examples 11, 13 and 17, it can be seen that the particle size distribution of the agglomerate material determined by the particle size analysis laser diffraction method is unimodal, with the unimodal peak located at 7-13 μm, which can further improve the energy density of the battery, and the battery has excellent rate performance.

[0289] It can be seen from Examples 1 to 20 that the particle size distribution of the agglomerate material satisfies 1.6≤(Dv90-Dv10) / Dv50≤2.3, the electrode has a high surface density and low elongation, the battery has a high energy density and excellent rate performance, and the electrochemical performance of the battery is comprehensively improved.

[0290] From the comparison between Example 4 and Example 5, it can be seen that the particle size distribution of the agglomerate material satisfies 1.8≤(Dv90-Dv10) / Dv50≤2.1, which can further improve the energy density of the battery.

[0291] From Examples 1 to 20, it can be seen that the specific surface area of ​​the aggregate material is 0.5 m 2 / g-0.9m 2 / g, the electrode can have a high surface density and low elongation, the battery has a high energy density and excellent rate performance, and the electrochemical performance of the battery is comprehensively improved.

[0292] It can be seen from Examples 1 to 20 that the elongation of the positive electrode plate in the longitudinal direction is 7% to 8%. The plate has a low elongation, which improves the processing performance of the plate.

[0293] From Examples 1 to 20, it can be seen that the coating area density of the positive electrode film layer is 21.5 mg / cm 2 -32.5mg / cm 2, the electrode has a high surface density and the battery has a high energy density.

[0294] From Examples 1 to 20, it can be seen that the compaction density of the positive electrode sheet is 3.5 g / cm 3 -3.8g / cm 3 , the pole piece has high compaction density and the battery has high energy density.

[0295] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material includes an aggregate material, the chemical formula of which is Li a Ni x Co y M 1-x-y O2, wherein 0.6≤a≤1.2, 0.6≤x≤1, 0≤y≤0.4, -0.1≤b≤0.1, and M includes one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, Nb, and Mo; the primary particle size of the agglomerate material is 100-600nm, and the particle size distribution of the agglomerate material satisfies (Dv90-Dv10) / Dv50≥1.

6.

2. The positive electrode active material according to claim 1, characterized in that The chemical formula Li a Ni x Co y M 1-x-y O 2-b , 0.6≤a≤1.2, 0.8≤x≤1, 0≤y≤0.2, −0.1≤b≤0.1, optionally, 0.8≤a≤1.2, 0.93≤x≤0.98, 0≤y≤0.07, −0.1≤b≤0.

1.

3. The positive electrode active material according to claim 1 or 2, characterized in that: The primary particle size of the agglomerate material is 200-500nm.

4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The particle size Dv50 of the agglomerate material is 6-15 μm, and can be optionally 7-13 μm.

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The particle size distribution diagram of the agglomerate material measured by a particle size analysis laser diffraction method is unimodal, and the unimodal peak is located at 6-15 μm, and can be optionally 7-13 μm.

6. The positive electrode active material according to any one of claims 1 to 5, characterized in that: The particle size distribution of the agglomerate material satisfies 1.6≤(Dv90-Dv10) / Dv50≤2.

3. Optionally, the particle size distribution of the agglomerate material satisfies 1.8≤(Dv90-Dv10) / Dv50≤2.

1.

7. The positive electrode active material according to any one of claims 1 to 6, characterized in that: The specific surface area of ​​the aggregate material is 0.5-0.9m 2 / g.

8. The positive electrode active material according to any one of claims 1 to 7, characterized in that: The agglomerate material comprises a first agglomerate and a second agglomerate, the particle size Dv50 of the first agglomerate is 9-15 μm, and the particle size Dv50 of the second agglomerate is 4-8 μm.

9. The positive electrode active material according to claim 8, characterized in that The chemical formula of the first aggregate is Li a1 Ni x1 Co y1 M1 1-x1-y1 O 2-b1 , the chemical formula of the second aggregate is Li a2 Ni x2 Co y2 M2 1-x2-y2 O 2-b2 , x1 ≥ x2, Among them, 0.6≤a1≤1.2, 0.6≤x1≤1, 0≤y1≤0.4, -0.1≤b1≤0.1, 0.6≤a2≤1.2, 0.4≤x2≤1, 0≤y2≤0.6, -0.1≤b2≤0.1, M1 and M2 independently include one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, Nb and Mo.

10. The positive electrode active material according to claim 9, characterized in that The chemical formula of the first aggregate is Li a1 Ni x1 Co y1 M1 1-x1-y1 O 2-b1 , 0.8≤a1≤1.2, 0.94≤x1≤0.98, 0≤y1≤0.06, -0.1≤b1≤0.

1.

11. The positive electrode active material according to claim 9 or 10, characterized in that: The chemical formula of the second aggregate is Li a2 Ni x2 Co y2 M2 1-x2-y2 O 2-b2 , 0.8≤a2≤1.2, 0.93≤x2≤0.96, 0≤y2≤0.07, -0.1≤b2≤0.

1.

12. The positive electrode active material according to any one of claims 8 to 11, characterized in that The primary particle size of the first aggregate is larger than the primary particle size of the second aggregate.

13. The positive electrode active material according to any one of claims 8 to 12, characterized in that: The primary particle size of the first agglomerate is 100-1000 nm, and the primary particle size of the second agglomerate is 100-300 nm.

14. The positive electrode active material according to any one of claims 8 to 13, characterized in that: The particle size distribution of the first agglomerate and the second agglomerate satisfies (Dv90-Dv10) / Dv50≤1.

50.

15. The positive electrode active material according to any one of claims 8 to 14, characterized in that: The particle size distribution of the first agglomerates satisfies 0.50≤(Dv90-Dv10) / Dv50≤1.30, and the particle size distribution of the second agglomerates satisfies 1.30≤(Dv90-Dv10) / Dv50≤1.

50.

16. The positive electrode active material according to any one of claims 8 to 15, characterized in that: The mass ratio of the first agglomerate to the second agglomerate is 1:1-9:

1. 17 . A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer comprises the positive electrode active material according to any one of claims 1 to 16.

18. The positive electrode sheet according to claim 17, characterized in that: The mass content of the positive electrode active material is 95% to 99.5%, based on the total mass of the positive electrode film layer.

19. The positive electrode sheet according to claim 17 or 18, characterized in that: The compaction density of the positive electrode sheet is 3.5 g / cm 3 -3.8g / cm 3 When the positive electrode sheet has a longitudinal elongation of 7% to 8%.

20. The positive electrode sheet according to any one of claims 17 to 19, characterized in that: The coating surface density of the positive electrode film layer is 21.5 mg / cm 2 -32.5mg / cm 2 .

21. The positive electrode sheet according to any one of claims 17 to 20, characterized in that: The compaction density of the positive electrode sheet is 3.5 g / cm 3 -3.8g / cm 3 .

22. A secondary battery, characterized in that: It includes a positive electrode plate, and the positive electrode plate is the positive electrode plate according to any one of claims 16 to 21.

23. The secondary battery according to claim 22, characterized in that: The secondary battery includes a lithium ion battery.

24. An electrical device, characterized in that: Includes the secondary battery according to claim 22 or 23.

Citation Information

Patent Citations

  • High-compaction-density positive electrode material and electrochemical energy storage device

    CN111384372A

  • Positive pole piece for secondary battery, secondary battery, battery module, battery pack and device

    CN114256443A

  • Positive electrode active material for high-strength lithium ion secondary battery, and lithium ion secondary battery arranged by use thereof

    JP2019169412A

  • Positive electrode material, electrochemical device containing same, and electronic device

    US20210280848A1